Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

enter image description here

My answer is: $[(1+x^2)^3]y = \dfrac{(1+x^2)^3}3+C$
But this option is not given, so is it correct?


share|improve this question
I got the same answer as you. I don't understand why they haven't got our one in the options. I solved it by multiplying through by an integrating factor. Namely, $$ \exp \left( \displaystyle \int \dfrac{6x}{1+x^2} \text{ d}x \right)$$ –  Khallil Benyattou Sep 1 at 1:16
The answer should be $a$. –  Mhenni Benghorbal Sep 1 at 2:16
I think that your solution is equivalent to $(a)$. Try expanding out the $(1+x^2)^3$ part. –  columbus8myhw Sep 1 at 4:13
I see thanks for the help –  Lim Zhi Jian Sep 1 at 4:47

3 Answers 3

$$(1+x^2) \frac{dy}{dx}=2x-6xy \Rightarrow (1+x^2) \frac{dy}{dx}=2x(1-3y) \Rightarrow \frac{dy}{1-3y}=\frac{2x}{1+x^2} dx \\ \Rightarrow -\frac{1}{3} \ln |1-3y|=\ln |1+x^2|+c$$

share|improve this answer
Thanks for the help. –  Lim Zhi Jian Sep 1 at 4:47

$$(1+x^2)\frac{dy}{dx}+6xy=2x \Rightarrow (1+x^2)\frac{dy}{dx}=2x-6xy \Rightarrow (1+x^2)\frac{dy}{dx}=2x(1-3y) \Rightarrow \frac{1}{1-3y}dy=\frac{2x}{1+x^2}dx \Rightarrow \int \frac{1}{1-3y}dy=\int \frac{2x}{1+x^2}dx \\ \Rightarrow \frac{-1}{3}\ln{|1-3y|}=\ln{|1+x^2|}+c\Rightarrow \ln{|1-3y|}^{\frac{-1}{3}}=\ln{|1+x^2|}+c \\ \Rightarrow e^{\ln{|1-3y|}^{\frac{-1}{3}}}=e^{\ln{|1+x^2|}+c } \\ \Rightarrow |1-3y|^{\frac{-1}{3}}=C|1+x^2|, C=e^c$$

Solve now for $y$.

share|improve this answer
After the third implication it should be $1+x^2$ I guess –  Freeze_S Sep 1 at 1:22
You're right! I edited my answer.. –  Mary Star Sep 1 at 1:51
Thanks for the help. –  Lim Zhi Jian Sep 1 at 4:53

$$\begin{align} (1+x^2)\frac{dy}{dx}+6xy&=2x\\ (1+x^2)\frac{dy}{dx}&=2x(1-3y)\\ \int \frac{dy}{1-3y}&=\int\frac {2x}{1+x^2}dx\\ -\frac13\ln(1-3y)&=\ln(1+x^2)\\ (1-3y)(1+x^2)^3&=0\\ (1+x^2)^3&=3y(1+x^2)^3\\ 1+3x^2+3x^4+x^6&=3y(1+x^2)^3\\ \frac 13+x^2+x^4+\frac{x^6}3&=y(1+x^2)^3\\ y(1+x^2)^3&=x^2+x^4+\frac{x^6}3+C \end{align}$$

i.e. option (A) $\blacksquare$.

Check by differentiating:

$$\begin{align} (1+x^2)^3\frac{dy}{dx}+6xy(1+2x^2)^2&=2x+4x^3+2x^5\\ &=2x(1+2x^2+x^4)\\ &=2x(1+x^2)^2\\ (1+x^2)\frac{dy}{dx}+6xy&=2x \end{align}$$

which is the original equation, hence solution is correct.

share|improve this answer
Thanks for the help –  Lim Zhi Jian Sep 1 at 4:46
you're most welcome :) –  hypergeometric Sep 1 at 4:48

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.